"Don't Know" Responses to Risk Perception Measures: Implications for Underserved Populations. (February 2013) - Waters, Erika A.; Hay, Jennifer L.; Orom, Heather; Kiviniemi, Marc T.; Drake, Bettina F.
Background: Risk perceptions are legitimate targets for behavioral interventions because they can motivate medical decisions and health behaviors. However, some survey respondents may not know (or may not indicate) their risk perceptions. The scope of "don't know" (DK) responding is unknown.Objective: Examine the prevalence and correlates of responding DK to items assessing perceived risk of colorectal cancer.Methods: Two nationally representative, population-based, cross-sectional surveys (2005 National Health Interview Survey [NHIS]; 2005 Health Information National Trends Survey [HINTS]), and one primary care clinic-based survey comprised of individuals from low-income communities. Analyses included 31, 202 (NHIS), 1, 937 (HINTS), and 769 (clinic) individuals.Measures: Five items assessed perceived risk of colorectal cancer. Four of the items differed in format and/or response scale: comparative risk (NHIS, HINTS); absolute risk (HINTS, clinic), and "likelihood" and "chance" response scales (clinic). Only the clinic-based survey included an explicit DK response option.Results: "Don't know" responding was 6.9% (NHIS), 7.5% (HINTS-comparative), and 8.7% (HINTS-absolute). "Don't know" responding was 49.1% and 69.3% for the "chance" and "likely" response options (clinic). Correlates of DK responding were characteristics generally associated with disparities (e.g., low education), but the pattern of results varied among samples, question formats, and response scales.Limitations: The surveys were developed independently and employed different methodologies and items. Consequently, the results were not directly comparable. There may be multiple explanations for differences in the magnitude and characteristics of DK responding.Conclusions: "Don't know" responding is more prevalent in populations affected by health disparities. Either not assessing or not analyzing DK responses could further disenfranchise these populations and negatively affect the validity of research and the efficacy of interventions seeking to eliminate health disparities.